2022
DOI: 10.1111/jne.13170
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric parameters from [18F]FDG PET/CTpredicts survival in patients with high‐grade gastroenteropancreatic neuroendocrine neoplasms

Abstract: A positive fluorine-18 labelled 2-deoxy-2-fluoroglucose ([ 18 F]FDG) positron emission tomography/computed tomography (PET/CT) has been associated with more aggressive disease and less differentiated neuroendocrine neoplasms (NEN). Although a high maximum standardized uptake value (SUV max ) predicts poor outcome in NEN, volumetric parameters from [ 18 F]FDG PET have not been evaluated for prognostication in a pure high-grade gastroenteropancreatic (GEP) NEN cohort. In this retrospective observational study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 59 publications
(115 reference statements)
1
16
0
Order By: Relevance
“…In a recent study, Stokmo et al. evaluated 66 patients with high-grade GEP NEN, and found MTV and TLG were also stronger prognostic parameters than SUVmax ( 21 ). Several studies also reported the prognostic value of SUVmax in NEN with higher SUVmax predicting poor outcome ( 22 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Stokmo et al. evaluated 66 patients with high-grade GEP NEN, and found MTV and TLG were also stronger prognostic parameters than SUVmax ( 21 ). Several studies also reported the prognostic value of SUVmax in NEN with higher SUVmax predicting poor outcome ( 22 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…A GI‐NEC score to prognosticate overall survival included five variables: presence of liver metastases, ALP, LDH, PS and Ki‐67, and identified two distinct patient cohorts 37 . 18 F‐FDG‐PET avid disease correlates with worse prognosis in NEC patients 38 . Emerging data show a possible benefit of analyzing gene mutations, which may possibly guide treatment 7,8 .…”
Section: Prognosis and Prognostic Factorsmentioning
confidence: 99%
“…37 18 F-FDG-PET avid disease correlates with worse prognosis in NEC patients. 38 Emerging data show a possible benefit of analyzing gene mutations, which may possibly guide treatment. 7,8 In contrast to colorectal adenocarcinoma, BRAF V600E mutations do not seem to be prognostic for colorectal NEC and few prognostic molecular markers have been found for digestive NEC.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…Patient cohort Patients were identified from a single institutional cohort at Oslo University Hospital, also included in two multi-institutional Nordic NEC registries organized by the Nordic Neuroendocrine Tumor Group, previously described by [8]. In short, this cohort consisted of 192 patients included between January 2000 and July 2018, with GEP NEC classified according to the WHO 2010-classification [28].…”
Section: Gep Nen Datasetmentioning
confidence: 99%
“…The prognosis for patients with advanced GEP NEC is poor, with a median survival of less than 12 months [5,6], whilst the prognosis for locoregional GEP NEC is higher; 20.7 months [7]. Numerous recently published studies [5,[8][9][10][11][12][13][14] have shown the prognostic importance of several parameters on overall survival (OS) such as age, performance status (PS), primary tumor site, tumor differentiation, TNM-stage, serum lactate dehydrogenase (LDH), serum platelet levels, proliferation marker Ki-67, maximum standardized uptake value (SUV max ), total metabolic tumor volume (tMTV) and total total lesion glycolysis (tTLG). Establishing more robust prognostic parameters and validating established parameters is essential to provide optimal care for this patient group.…”
Section: Introductionmentioning
confidence: 99%